UNESCO Courier - Transforming Ideas - United Nations Educational, Scientific; Cultural Organization (United Nations, 2022)
Throughout UNESCO’s 75 years of existence, never before has the Courier, UNESCO’s flagship magazine, published an anthology, in book form, with such scope and scale. These two volumes bring together some of the great thinkers and pioneering minds of recent times who have led important discussions on society’s pressing challenges. UNESCO Courier: Transforming Ideas will lead you through an exciting, magical and thought-provoking adventure into UNESCO’s past, present and future.